Predominant dendriform pulmonary ossification in a usual interstitial pneumonia-like distribution : to be distinguished from idiopathic pulmonary fibrosis - Slabbynck, Hans; de Beukelaar, Tom; De Surgeloose, Didier; Van Goethem, Jozef; Charels, Karina; Bedert, Lieven; Wuyts, Wim (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Idiopathic dendriform diffuse pulmonary ossification (DPO) is a rare disorder. High resolution CT (HRCT) with appropriate osteoporosis window setting reveals the diagnosis. We report the features of eight patients, of whom two brothers, with HRCT findings compatible with predominant DPO in a bibasal subpleural distribution (usual interstitial pneumonia (UIP)-like distribution) and review the literature for DPO in this UIP-like distribution. DPO in a UIP-like distribution seems to be a disorder of the very old (age 75-87 (mean 83.6) male (8 out of 8), with familial occurrence, with associated cardiovascular disease and frequent use of anticoagulants as common findings, and with a slowly progressive nature and the absence of radiological honeycombing despite long lasting disease contrasting with idiopathic pulmonary fibrosis (IPF). Idiopathic pulmonary fibrosis (IPF) should be differentiated from predominant DPO in a UIP-like distibution.